WRKY Transcription Factors Associated With NPR1-Mediated Acquired Resistance in Barley Are Potential Resources to Improve Wheat Resistance to Puccinia triticina - Gao, Jing; Bi, Weishuai; Li, Huanpeng; Wu, Jiaojiao; Yu, Xiumei; Liu, Daqun; Wang, Xiaodong (Frontiers in Plant Science, 2018)
Systemic acquired resistance (SAR) in Arabidopsis is established beyond the initial pathogenic infection or is directly induced by treatment with salicylic acid or its functional analogs (SA/INA/BTH). NPR1 protein and WRKY transcription factors are considered the master regulators of SAR. Our previous study showed that NPR1 homologs in wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) regulated the expression of genes encoding pathogenesis-related (PR) proteins during acquired resistance (AR) triggered by Pseudomonas syringae pv. tomato DC3000. In the present examination, AR induced by P. syringae DC3000 was also found to effectively improve wheat resistance to Puccinia triticina (Pt). However, with more complex genomes, genes associated with this SAR-like response in wheat and barley are largely unknown and no specific WRKYs has been reported to be involved in this biological process. In our subsequent analysis, barley transgenic line overexpressing wheat wNPR1 (wNPR1-OE) showed enhanced resistance to Magnaporthe oryzae isolate Guy11, whereas AR to Guy11 was suppressed in a barley transgenic line with knocked-down barley HvNPR1 (HvNPR1-Kd). We performed RNA-seq to reveal the genes that were differentially expressed among these transgenic lines and the wild-type barley plants during the AR. Several PR and BTH-induced (BCI) genes were designated as downstream genes of NPR1. The expression of few WRKYs was significantly associated with NPR1 expression during the AR events. The transient expression of three WRKY genes, including HvWRKY6, HvWRKY40, and HvWRKY70, in wheat leaves by Agrobacterium-mediated infiltration enhanced the resistance to Pt. In conclusion, a profile of genes associated with NPR1-mediated AR in barley was drafted and WRKYs discovered in the current study showed a substantial potential for improving wheat resistance to Pt.